Challenging Ciscentric Feminist Margins: A South African Study on Gender-Based Violence in the Lives of Black Trans Women - Shabalala, Siyanda B.; Boonzaier, Floretta; Chirape, Skye (PINS-Psychology in Society, 2023)
Feminist discourses around the scourge of gender-based violence (GBV) have historically prioritized the voices and contextualities of cisgender heterosexual women, often to the exclusion of trans persons. In light of the continual invisibility of black trans persons and in particular black trans women in anti-GBV activism, this paper explores black trans women’s experiences of violence in post-apartheid South Africa. The study was undertaken from a transfeminist framework that asserts that the stories and histories of trans persons are central to the development of trans epistemologies within an inclusive gender liberation framework. The study followed a narrative methodological approach. Unstructured individual interviews were conducted with eight black trans women living in South Africa. Narratives of gender policing and punitive sexual violence in addition to narratives of cissexism as well as of the paradoxical hypervisibility and invisibility of black trans positions revealed violence meted against black trans women in South Africa as structural, grounded on a patriarchal matrix of cisgender power representing trans women as devalued others. Apartheid legacies of racialised economic marginalisation manifest as bearing a strong mediating role in shaping black trans women’s sustained vulnerability to violence. By addressing anti-trans violence as a feminist concern, this paper disrupts the ciscentricism of feminism, enabling more nuanced and inclusive constructions of GBV.